Assessing the impacts of different land uses and soil and water conservation interventions on runoff and sediment yield at different scales in the central highlands of Ethiopia - Yaekob, Tesfaye; Tamene, Lulseged D.; Gebrehiwot, Solomon G.; Demissie, Solomon S.; Adimassu, Zenebe; Woldearegay, Kifle; Mekonnen, Kindu; Amede, Tilahun; Abera, Wuletawu; Recha, John W.M.; Solomon, Dawit; Thorne, Peter J. (Cambridge University Press, 2022)
To tackle the problem of soil erosion and moisture stress, the government of Ethiopia introduced a yearly mass campaign where communities get together and implement various soil and water conservation (SWC) and water harvesting (WH) practices. Although the interventions are believed to have reduced soil erosion/sediment yield and enhanced surface and ground water, quantitative information on the impacts of various options at different scales is scarce. The objective of this study was to assess the impacts different land uses, SWC and WH interventions on water and suspended sediment yield (SSY) at plot and watershed scales in the central highlands of Ethiopia. Standard erosion plot experiments and hydrological stations were used to monitor the daily water and SSY during 2014 to 2017. The results show differences between treatments both at plot and watershed scales. Runoff and soil loss were reduced by an average 27 and 37%, respectively due to SWC practices at the plot level. Overall, SWC practices implemented at the watershed level reduced sediment yield by about 74% (in the year 2014), although the magnitude of sediment reduction due to the SWC interventions reduced over time. At both scales it was observed that as the number of years since SWC measures have been in place increased, their effectiveness declined due to the lack of maintenance. This study also revealed that extrapolating of plot data to watershed scale causes over or under estimation of net erosion.